2008
DOI: 10.1080/00016340801908783
|View full text |Cite
|
Sign up to set email alerts
|

Placental pathology in women with gestational diabetes

Abstract: Histological abnormalities were observed more frequently in the diabetic placentas compared to the controls. These findings support the hypothesis that impaired placental function is one of the main reasons for the increased frequency of fetal complications in diabetic pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
103
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(121 citation statements)
references
References 14 publications
13
103
2
3
Order By: Relevance
“…We also confirmed that chorangiosis has been associated with normoblastemia of fetal blood. 9 Interestingly, frequencies of maternal diabetes mellitus were similar in all 3 groups, which confirms not only that chorangiosis is common in diabetic placentas, 1,11,40 but also that the various degrees of control of diabetes mellitus and/ or superimposed preeclampsia may have an impact on placental morphology that would lead to inclusion into either group 1, group 2 or group 3. Poorly controlled cases of maternal diabetes mellitus were most likely to fall in group 1, those complicated by hypertensive diseases into group 2, and those apparently well controlled and without complications into group 3.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…We also confirmed that chorangiosis has been associated with normoblastemia of fetal blood. 9 Interestingly, frequencies of maternal diabetes mellitus were similar in all 3 groups, which confirms not only that chorangiosis is common in diabetic placentas, 1,11,40 but also that the various degrees of control of diabetes mellitus and/ or superimposed preeclampsia may have an impact on placental morphology that would lead to inclusion into either group 1, group 2 or group 3. Poorly controlled cases of maternal diabetes mellitus were most likely to fall in group 1, those complicated by hypertensive diseases into group 2, and those apparently well controlled and without complications into group 3.…”
Section: Resultssupporting
confidence: 49%
“…7,8 It has been related to several chronic obstetric complications and outcomes, 4 to mention only perinatal deaths, maternal diabetes mellitus, chronic infection, in utero asphyxia, umbilical cord problems, congenital anomalies, fetal vascular thrombosis, maternal anemia, smoking, air pollution, and multiple pregnancy. 7,[9][10][11][12][13][14][15][16][17][18][19][20] The incidence of chorangiosis is low in the second trimester and increases in the third trimester, 21 in which it is lower in preterm than in term pregnancies. 22 Chorangiosis has statistically nonsignificantly clustered with preuterine hypoxia, multiple pregnancy, and normoblasts in fetal circulation.…”
mentioning
confidence: 99%
“…21,39 The pattern is evoked by maternal hypoxemia secondary to decreased oxygen pressure in the environment (pregnancies at high altitudes), decreased oxygen binding capacity of the maternal blood (maternal anemia), air pollution and maternal smoking, increased distension of the uterus (multiple pregnancy), and maternal diabetes mellitus (abnormal oxygen-hemoglobin dissociation curve). 21,[38][39][40][41][42][43][44] Clusters of multinucleate giant cells in the decidua basalis and excessive numbers of extravillous trophoblasts are less commonly seen in this than in other patterns of diffuse hypoxic placental injury, 21 most likely because of the association of PR with deep trophoblastic, myometrial invasion, which was proven, at least in maternal anemia. 45 This pattern has a better prognosis than other types of chronic hypoxic injury, 21 probably because of hypoxic preconditioning and resistance to ischemia-reperfusion injury during labor, as was proven in pregnancies at high altitudes 46 and multiple pregnancies.…”
Section: Patterns Of Chronic Hypoxic Placental Injurymentioning
confidence: 99%
“…Impaired reproductive performance is a well-known result of the diabetic syndrome in many mammalian species, including humans (Chieri et al 1969;Kirchick et al 1978;Vomachka and Johnson 1982;Garris et al 1986). Placental dysfunction contributes to an increased frequency of fetal complications in diabetic pregnancies (Daskalakis et al 2008).…”
Section: Introductionmentioning
confidence: 99%